From innovativeness to insecurity: unveiling the facets of translation technology use behavior among EFL learners using TRI 2.0 - Junfeng Zhao; Xiang Li; Zhaoyang Gao (Humanities & Social Sciences Communications)
Abstract Translation technologies are essential in supporting English as a Foreign Language (EFL) students by overcoming language barriers and enhancing academic performance. Despite their potential benefits, the actual use behavior of these technologies is underexplored in the existing literature. This study investigates the drivers and inhibitors of translation technology use behavior among college EFL students by pioneering the application of the Technology Readiness Index (TRI) 2.0 framework. A structured questionnaire was administered to 554 junior and senior EFL students across six Chinese universities. Data were analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural models and a multigroup analysis (MGA) to examine potential differences based on socioeconomic background. The results showed that optimism positively influenced behavioral intention (β = 0.251, p < 0.001) and use behavior (β = 0.189, p < 0.001) regarding translation technologies. The innovation demonstrated a significant positive effect on behavioral intention (β = 0.113, p < 0.01) but not on use behavior. Discomfort negatively impacted behavioral intention (β = −0.276, p < 0.001) but did not significantly affect use behavior. Insecurity negatively influenced both behavioral intentions (β = −0.319, p < 0.001) and use behavior (β = −0.254, p < 0.001). Behavioral intention was a strong predictor of use behavior (β = 0.372, p < 0.001). MGA showed no statistically significant differences between rural and urban students in the proposed relationships. By identifying optimism and insecurity as key determinants of intention and actual usage, this study underscores the importance of cultivating technology readiness and providing targeted support to promote translation technology adoption in higher education, ultimately strengthening language-learning outcomes for EFL students.